Father-and-son’s Conflicts in Webtoon Bastard - Ivania Tanoko (Institute of Research and Community Outreach - Petra Christian University, 2021)
Webtoon is a popular digital-comic media. For this thesis, I will analyze a thriller Webtoon Bastard because it has a great theme, plot, drawing style, and good reviews. The story focuses on the conflicts between a father (Dongsoo Seon), who is also a murderer, and his son (Jin Seon), which inspires me to take the failure in a father-and-son’s relationship as my topic. Therefore, I want to explore what factors trigger father-and-son’s conflicts and how those factors lead to the failure in the father-and-son’s relationship. I apply the theory of father-and-son’s conflict. I want to show Dongsoo’s and Jin’s different ways of thinking on concepts of happiness and love, parental roles, and parental authority create conflicts because of no emotional bond and agreement related to familism values, discrepancy between expectations and reality, and no room for adolescent’s independence. In conclusion, the complexity in this relationship can attract Webtoon’s readers. Keywords: father and son, single parent, adolescent, conflicts in the family, webtoon